The Effect of the Traditional Papuan Game Patah Kaleng on the Numeracy Skills of Children Aged 5–6 Years - Yul Fitriana; Syamsulrizal Syamsulrizal; Alman Alman (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the effect of the Papua traditional game Patah Kaleng on the numeracy skills of children aged 5–6 years at TK UNIMUDA Alam Mentari. The background of this research is the low level of early childhood numeracy skills, which are still dominated by conventional learning approaches that are less contextual and lack play-based activities. This study employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The research subjects consisted of 15 children in the experimental class and 16 children in the control class. Data were collected using a numeracy observation instrument based on 10 indicators with a Likert scale. The results showed that both groups experienced an improvement in numeracy skills; however, the increase in the experimental class was more significant. The mean score of the experimental class increased from 20.53 to 31.47 with a gain (Δ) of 10.93, while the control class increased from 19.81 to 23.44 with a gain (Δ) of 3.63. The results of the paired sample t-test indicated a significance value (p < 0.05), meaning that the research hypothesis was accepted. In conclusion, the Papua traditional game Patah Kaleng has a significant effect on improving early childhood numeracy skills. These findings imply that traditional game-based learning can serve as an effective and contextual strategy to enhance numeracy skills while supporting the development of culturally responsive learning in early childhood education